STUDENTS’ PERCEPTION OF POWERPOINT USE IN VOCABULARY MASTERY - Amar, Nurmalayanti; Sakkir, Geminastiti; Radhiyani, Fitri (Universitas Negeri Makassar, 2022)
This research aims to find out students’ perception of PowerPoint use in vocabulary mastery at SMPN 17 Makassar especially for ninth-grade students. This research employed a qualitative research design to investigate students’ perception of PowerPoint use in vocabulary mastery. The data was collected through interviews and documentation. The results showed that students' perceptions of the use of PowerPoint applications in their learning English activities are positive. Students perceived that PowerPoint uses benefited them in several ways through engaging their attention, creating an interactive learning atmosphere, sustaining word retention, and increasing students’ practicing time.